Nicholas Trevet's Commentary on the psalms (1317-c.1321): a publishing history - Kujawiński, Jakub (Instrumenta patristica et mediaevalia, 2023)
Shortly after 1317, Nicholas Trevet, an English Dominican friar and Oxford master, was commissioned by his provincial prior to write a literal commentary on the Psalter. He chose as his reference version the less commonly used Latin translation by Jerome from the Hebrew, and delivered his work before 1321/22. This study will be the first book-length examination of Trevet?s commentary. The focus is on publication, the ways in which the work was circulated by the author and his proxies. 0Through a combined analysis of codicological, textual, and historical features of the nine fourteenth-century manuscripts, the book seeks to capture and appreciate contemporary efforts to make Trevet?s work available to readers within and without the Dominican Order, in England and on the Continent. Already in the author?s lifetime the commentary was being copied in Paris and reached readerships in Avignon and probably in Naples. It is argued that the joint publishing endeavours of Trevet and his contemporaries laid solid foundations for a wide reception, and that other factors must have prevented the work from achieving any durable success